Laser Ablated Citrate-Stabilized Silver Nanoparticles Display Size and Concentration Dependant Biological Effects - Jelena Filipović Tričković; Miloš Momčilović; Gordana Joksić; Sanja Živković; Bojana Ilić; Miloš Ognjanović; Mirjana Novaković; Ana Valenta Šobot (Nanomaterials and Nanotechnology)
Silver nanoparticles (AgNPs) have been recognized for widespread biological applications due to their antimicrobial and anti-inflammatory effect, especially in dentistry and for wound healing. Many features determine their beneficial or toxic potential, such as their synthesis type, size, morphology, coating, and concentration. Most synthesis types rely on the use of synthetic chemicals, which contributes to their toxicity. We present an environmentally friendly method for “green” synthesis of AgNPs from the silver target by pulsed laser ablation in liquid (PLAL) using citrate as the stabilizing agent. Since AgNPs already have many dental applications, we examined their antibacterial effect against supragingival biofilm-forming bacteria and bacterial strains known to cause resistant dental infections. Their impact on human fibroblast cells’ cytotoxicity, proliferation (measured by XTT and Ki-67 immunofluorescence), pro/antioxidant balance, and lipid peroxidation (measured by PAB and LPP) was evaluated. AgNPs1 (21 nm) and AgNPs2 (15 nm) spherical nanoparticles with good overall stability were obtained. The highest tested dose of smaller nanoparticles (AgNPs2) displays not only an effective antibacterial effect against the tested oral bacteria strains but also a pro-oxidant and cytotoxic effect on fibroblast cells. Lower doses do not affect bacterial survival but increase the cell proliferation and metabolic activity and show an antioxidative effect, suggesting that different concentrations display a substantially opposite effect. Compared to larger AgNPs1, smaller AgNPs2 possess more potent biological effects, indicating that size plays a pivotal role in their activity. Such opposite outcomes could be important for their medical application, and high concentrations could be used for the inhibition of dental biofilm formation and resistant dental infections as well as proliferative conditions, while low doses could be beneficial in the treatment of atrophic and inflammatory disorders. Finally, we showed that silver-targeted PLAL, using citrate as a stabilizing agent, produces biologically potent nanoparticles that could have many applications depending on their size and concentration.